Systemic treatments for non-melanoma skin cancers (Canadian Dermatology Today, 2022)
One in every 3 cancers diagnosed, including both melanoma and non-melanoma, is a skin cancer. Non-melanoma skin cancer (NMSC) which includes basal cell carcinoma (BCC), squamous cell carcinoma (SCC) and, among others, other rarer NMSC such as Merkel cell carcinoma (MCC), represents the majority of skin cancers diagnosed in Canada and globally. NMSC is not included in most provincial and territorial cancer registries making it difficult to characterize the incidence and outcomes. Dermatologists across Canada manage NMSC daily with topical and surgical treatments. However, in rare cases these tumours can progress to become unresectable, locally destructive, metastasize and even cause death. For NMSC that progresses, there are systemic treatment options to help manage these malignancies. The aim of this article is to review the common systemic treatments for management of locally advanced, unresectable and/or metastatic NMSCs.